Modulating the Effect of β-Sitosterol Conjugated with Magnetic Nanocarriers to Inhibit EGFR and Met Receptor Cross Talk - Shanmuga Sundari Ilangovan; Biswanath Mahanty; Venkatesan Perumal; Shampa Sen (MDPI AG, 2023)
The cross-talk between the EGFR (Epidermal Growth Factor Receptor) and MET (Hepatocyte Growth Factor Receptor) poses a significant challenge in the field of molecular signaling. Their intricate interplay leads to dysregulation and contributes to cancer progression and therapeutic resistance. β-Sitosterol (BS), a plant sterol with promising anticancer properties, shows increased research on its potential as a chemopreventive agent. However, significant modifications are required to deliver BS in cancer cells due to its lower efficacy. The present work aims to design a carrier-mediated delivery system specifically targeting cancer cells with EGFR and MET receptor cross-talk. Surface modification of BS was performed with superparamagnetic iron oxide nanoparticles (SPIONs), polyethylene glycol (PEG), and poly(N-isopropylacrylamide) (PNIPAM) to enhance the delivery of BS at the target site. BS was conjugated with SPIONs (BS-S), PNIPAM (BS-SP), PEG, and PNIPAM (BS-SPP) polymers, respectively, and the conjugated complexes were characterized. Results showed an increase in size, stability, and monodispersity in the following order, BS-S, BS-SP, and BS-SPP. The drug encapsulation efficiency was observed to be highest in BS-SPP (82.5%), compared to BS-S (61%) and BS-SP (74.9%). Sustained drug release was achieved in both BS-SP (82.6%) and BS-SPP (83%). The IC 50 value of BS, BS-S, BS-SP, and BS-SPP towards MCF 7 was 242 µg/mL,197 µg/mL, 168 µg/mL, and 149 µg/mL, HEPG2 was 274 µg/mL, 261 µg/mL, 233 µg/mL and 207 µg/mL and NCIH 460 was 191 µg/mL, 185 µg/mL, 175 and 164 µg/mL, indicating highest inhibition towards NCIH 460 cells. Our results conclude that β-sitosterol conjugated with SPION, PEG, and PNIPAM could be a potential targeted therapy in inhibiting EGFR and MET receptor-expressing cancer cells.